Luxury brands in online gaming: Enhancing perceived quality of luxury products - Rodrigues, M. B.; Loureiro, S. M. C.; Guerreiro, J.; Romero, M. I. R. (Global Fashion Management Conference Proceeding, 2024)
Over the past two decades, the luxury industry has undergone significant transformations. To maintain consumer engagement and visibility, luxury brands are now exploring the digital entertainment space, complementing their traditional strengths with a digital presence (Gilliland, 2020). In early 2019, Moschino released a capsule collection featuring iconic Sims motifs, which were later sold within the Sims game. Following this, Louis Vuitton became a trailblazer by selling “skins” in the League of Legends game. Skins are graphic downloads that alter the appearance of ingame characters. Subsequently, other renowned brands such as Gucci, Marc Jacobs, Valentino, and Balenciaga embraced this trend and collaborated with online games.